THE CORRELATION AMONG INTRAPERSONAL INTELLIGENCE, LEARNING STYLES, SELF- CONFIDENCE, AND SPEAKING ABILITY OF THE SECOND SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF PGRI UNIVERSITY OF PALEMBANG - Indawan Syahri; Mulyadi Mulyadi; Ayu Novitasari (Universitas PGRI Palembang, 2017)
This study was aimed to investigate the evidence about intrapersonal intelligence, learning styles, and self-confidence to speaking ability. This is quantitative study. The population of this study was all the second semester students of English Education Study Program of PGRI University of Palembang with the total of 60 students. For the purpose of this study, 60 students had been selected by using total sampling as the research sample. To collect the data, there were two kinds of instrument used. The first intrument was questionnaire used to collect the data of students’ intrapersonal intelligence, learning styles, and self-confidence. The second intrument was a speaking test to collect the data of students’ speaking ability. The data were analyzed by using Pearson Product Moment and multiple regression formula of SPSS 21 program to find out the correlation among intrapersonal intelligence, learning styles, and self-confidence on speaking ability. And the result indicated, there was significant correlation between intrapersonal intelligence and speaking ability with the correlation coefficient (r) was .965, between self-confidence and speaking ability it was also shown that the level of correlation was high category (r) .989, but there was not any significant correlation between learning styles and speaking ability with the correlation coefficient (r) was -.112. There were significante correlation among intrapersonal intelligence, learning styles, and self-confidence on speaking ability with the level of correlation analysis was in positive category (r) .991. The result suggests that intrapersonal intelligence, learning styles, and self-confidence significantly correlate with speaking ability.Keywords: Intrapersonal Intelligence, Learning Styles, Self- Confidence, and Speaking Ability.